Martensitic transformation during electrochemical polishing of metastable austenitic stainless steel. (15th February 2023) - Gwon, Hojun; Chae, Junyoung; Jeong, Chanwoo; Lee, Hyukjae; Kim, Dong Hwi; Anaman, Sam Yaw; Jeong, Dameul; Cho, Hoon-Hwe; Kwon, Young-Kyun; Kim, Sung-Joon; Han, Heung Nam
Abstract: We found that remarkable martensitic transformation occurs during electrochemical polishing (EP) in 16Cr-5Ni metastable austenitic stainless steel. It was observed through EBSD measurement that the α' martensite fraction increases as the applied voltage and EP time increase. Interestingly, upon comparing EBSD, XRD, and ferritescope measurements, it was confirmed that the martensitic transformation is confined to the surface where EP took place. To investigate the mechanism by which the EP process induces the martensitic transformation, COMSOL Multiphysics was used to calculate the electric charge distribution on the specimen surface under various applied voltages. In order to accurately consider the surface shape of the specimen, we used AFM for measurement of the three-dimensional space distribution of asperities, which was utilized as an initial condition of COMSOL Multiphysics simulation. Finally, through the first-principles calculations reflecting the obtained charge distribution in the surface region, it was concluded that significant stress could be developed due to the charge build-up on the surface, resulting in stress-induced martensitic transformation on the surface of the metastable austenitic stainless steel during EP. Graphical abstract: Image, graphical abstract .